The Impact of External Factors on the Epigenome: In Utero and over Lifetime. (18th May 2016) - Toraño, Estela G.; García, María G.; Fernández-Morera, Juan Luis; Niño-García, Pilar; Fernández, Agustín F.
Abstract : Epigenetic marks change during fetal development, adult life, and aging. Some changes play an important role in the establishment and regulation of gene programs, but others seem to occur without any apparent physiological role. An important future challenge in the field of epigenetics will be to describe how the environment affects both of these types of epigenetic change and to learn if interaction between them can determine healthy and disease phenotypes during lifetime. Here we discuss how chemical and physical environmental stressors, diet, life habits, and pharmacological treatments can affect the epigenome during lifetime and the possible impact of these epigenetic changes on pathophysiological processes.